PENGARUH PERENCANAAN ANGGARAN TERHADAP PENYERAPAN ANGGARAN PADA DINAS PENATAAN RUANG KOTA BANDUNG - Engkus; Endang Hermawan; Endah Dwi Rahmawati (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
This study aims to determine how much influence budget planning has on budget absorption. The method used in this research is quantitative research with an associative approach. Data collection techniques through literature study, observation and questionnaires. The questionnaire was distributed to 76 respondents, with the analysis technique is a simple linear regression coefficient. The results of this study have a significant influence between the dimensions of budget planning and budget absorption. With two-sided testing (significance = 0.05) the partial test results (t test) obtained t count > t table (12.582 > 1.995). In the simultaneous regression coefficient test (f test), the results of f count > f table (158.296 > 3.09) are obtained with a significant level of 0.000 < 0.05, so Ha is accepted, meaning that simultaneously there is a significant influence between budget planning and budget absorption. While the calculation of the coefficient of determination is 68.1%, the influence of budget planning on budget absorption is 68.1% and the remaining 31.9% is influenced or explained by other variables not examined by the researcher.